Environmental reservoirs and mechanisms of persistence of Vibrio cholerae - Lutz, Carla; Erken, Martina; Noorian, Parisa; Sun, Shuyang; McDougald, Diane (Frontiers in Microbiology, 2013)
It is now well accepted that Vibrio cholerae, the causative agent of the water-borne disease cholera, is acquired from environmental sources where it persists between outbreaks of the disease. Recent advances in molecular technology have demonstrated that this bacterium could be detected in areas where it had not been isolated from before, indicating a much broader, global distribution of this bacterium rather than specifically within regions where cholera is endemic. The environmental persistence of V. cholerae in the aquatic environment can be attributed to multiple intra- and interspecific strategies such as responsive gene regulation and biofilm formation on biotic and abiotic surfaces, as well as interactions with a multitude of other organisms. This review will discuss some of the mechanisms that enable the persistence of the bacterium in the sometimes hostile environment. In particular, we will discuss how V. cholerae can survive stressors such as starvation, temperature and salinity fluctuations as well as how the organism persists under constant predation by heterotrophic protists.